#### Answer

$\dfrac{1}{ w^7}$

#### Work Step by Step

(i) $(a^m)^n=a^{mn}$
(ii) $a^{-m} = \dfrac{1}{a^m}, a \ne 0$
Use the rules above to obtain:
$=w^{7 \cdot (-1)}
\\=w^{-7}
\\=\frac{1}{ w^7}$

Published by
Prentice Hall

ISBN 10:
0133500403

ISBN 13:
978-0-13350-040-0

$\dfrac{1}{ w^7}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.